2021
DOI: 10.5216/mh.v21.69145
|View full text |Cite
|
Sign up to set email alerts
|

Digital competence and the use of technological resources by teachers in music conservatories and schools of music

Abstract: At present, digital technology provides innumerable new possibilities in the field of musical education. Its tools are, without a doubt, a valuable mediator in teaching-learning processes at the levels of elementary and university education, and specialisation. This study examines the knowledge and use of technological resources in the specific sphere of teaching in elementary, intermediate and superior stages in music conservatories and schools of music. By means of an online questionnaire administered to 82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
7
0
3
Order By: Relevance
“…According to Anderson and Dron [ 23 ], mobile devices offer educational opportunities, but their impact on academic performance varies depending on how they are integrated into the learning process. Studies can be found in which technology improves performance in general [ 24 ] or in very specific areas in particular [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Anderson and Dron [ 23 ], mobile devices offer educational opportunities, but their impact on academic performance varies depending on how they are integrated into the learning process. Studies can be found in which technology improves performance in general [ 24 ] or in very specific areas in particular [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shifting to the theme of autonomy, García et al [ 25 ] proposed strategies to foster learner autonomy. Seguel [ 35 ], in contrast, investigated contexts where autonomy was discouraged, concluding that the training lacked adequate support to promote autonomy and that this affected performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The constant discoveries in digital technology enrich musicians' resources and training opportunities, but, at the same time, also bring new challenges for educational systems. The changes taking places in the realm of technology are most of the times complex, fast, abundant, with new approaches which challenge the teaching staff of art institutions to adapt in their turn and to offer up-to-date teaching methods without disregarding the option of technological aids (Fernandez, Isaac and Acero, 2021).…”
Section: Musicians' Interaction With Cyberculturementioning
confidence: 99%
“…3. Keele University -"Computer Science and Music Production"is a software type that aims attention at a deeper knowledge of programming techniques for music software, matrici perfecte, ce pot fi probate și combinate pentru a se crea un material original și chiar consistent.…”
unclassified
“…La diversidad en herramientas tecnológicas ha ocasionado que existan diversas formas de clasificación de las TIC. En educación, uno de los bloques que se señalan en algunas clasificaciones son los recursos educativos audiovisuales (García et al, 2021) incluidos también en clasificaciones que se centran en los recursos tecnológicos en la educación en danza (De las Heras-Fernández, 2022. p. 111). Además, algunas revisiones bibliográficas abordan los recursos tecnológicos en la enseñanza de la danza en los distintos contextos educativos (De las Heras-Fernández, et.…”
Section: Introductionunclassified